2014
DOI: 10.1039/c4fo00183d
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic activity of Taraxacum mongolicum associated with the activation of AMP-activated protein kinase in human HepG2 cells

Abstract: This study investigated the hypolipidemic effect and potential mechanisms of T. mongolicum extracts. T. mongolicum was extracted by refluxing three times with water (TM-1), 50% ethanol (TM-2) and 95% ethanol (TM-3). TM-2 contained components with the most effective hypolipidemic potentials in HepG2 cells. Extended administration of TM-2 stimulated a significant reduction in body weight and levels of serum triglyceride LDL-C and total cholesterol in rats. To evaluate the bioactive compounds, we successively fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“… 2013 ) and hypolipidemic (Liu et al. 2014 ) effects in HepG2 cells. These findings suggest that consumers can improve their health by choosing eggs selectively, not only to increase their intake of UFA, but also to prevent the occurrence of CVDs and CAD.…”
Section: Discussionmentioning
confidence: 99%
“… 2013 ) and hypolipidemic (Liu et al. 2014 ) effects in HepG2 cells. These findings suggest that consumers can improve their health by choosing eggs selectively, not only to increase their intake of UFA, but also to prevent the occurrence of CVDs and CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The TM extracts have been found useful for hypolipidemic effects due to their down-regulated expression of fatty acid synthase and the inhibiting activity of acetyl-coenzyme A carboxylase through the phosphorylation of AMP-activated protein kinase (Liu et al. 2014 ). In vivo and in vitro studies showed that SM extracts, such as tanshinone IIA and salvianolate, induce anti-oxidative and anti-inflammatory effects (Ren et al.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro; 0, 50, 100, 200, and 400 mg•mL −1 It possessed the most effective hypolipidemic activity in HepG2 cells. [111] Chlorogenic acids T. antungense…”
Section: Ethanol Extracts T Mongolicummentioning
confidence: 99%